2021
DOI: 10.21203/rs.3.rs-145584/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Neural Correlates of Product Attachment to Cosmetics: Is It Similar to That of Attachment in Human Relationships?

Abstract: We used functional magnetic resonance imaging to investigate the similarities in the attachment toward individual's favorite cosmetics and beloved person, both of which are reinforced by touch-driven behaviors. We conducted 2 (visual and visual with tactile) × 2 (preferred and non-preferred cosmetics) experiments. Thereafter, we set regions of interest as per previous studies of human relationship attachment and tested their significance. The hippocampus, posterior cingulate cortex (PCC), putamen, periaqueduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 53 publications
(91 reference statements)
0
2
0
Order By: Relevance
“…Based these results, we suggest that the attachment to the products were generated during the DIY experience and the memory of the DIY experience was recalled by looking at pictures of the DIY products during the WTP measurement. On the other hand, Kikuchi et al (2021) described a positive correlation between brain areas related to memory (PCC-anterior hippocampus connectivity) and evaluation of attachment and revealed that greater product attachment evoked increased connectivity in memory-related regions. Unfortunately, the current study could not examine activations of these areas because they are located beyond the reach of near-infrared light.…”
Section: Cortical Activations Related To Ikea E Ectmentioning
confidence: 99%
See 1 more Smart Citation
“…Based these results, we suggest that the attachment to the products were generated during the DIY experience and the memory of the DIY experience was recalled by looking at pictures of the DIY products during the WTP measurement. On the other hand, Kikuchi et al (2021) described a positive correlation between brain areas related to memory (PCC-anterior hippocampus connectivity) and evaluation of attachment and revealed that greater product attachment evoked increased connectivity in memory-related regions. Unfortunately, the current study could not examine activations of these areas because they are located beyond the reach of near-infrared light.…”
Section: Cortical Activations Related To Ikea E Ectmentioning
confidence: 99%
“…For this reason, we refer to two types of previous studies. Kikuchi et al (2021) used fMRI to measure brain regions associated with attachment to cosmetics and reported that the left ventral pallidum (L-VP) and right posterior cingulate cortex (R-PCC) were activated. Minagawa-Kawai et al (2008) used fNIRS to measure brain functions related to attachment between mothers and infants and reported that the anterior orbitofrontal cortex (OFC) was activated.…”
Section: Introductionmentioning
confidence: 99%